Vibration exercise: The potential benefits - Cochrane, D. J. (International Journal of Sports Medicine, 2011)
The aim of this review was to examine the physiological effects of vibration exercise (VbX), including the cardiovascular indices and to elucidate its potential use for those with compromised health. VbX has long been acknowledged as a potential modality in sport, exercise, and health sectors. Muscle force and power have been shown to increase after VbX for athletes, the aged and those with diseases, where neural factors are thought to be the main contributor. Further, similarities to the tonic vibration reflex have been used to propose that the muscle spindle plays a role in activating the muscle which could benefit those with compromised health. There is strong evidence that acute VbX can enhance upper and lower-body muscle power, and there is some indication that longer-term VbX can augment muscle power of upper and lower body extremities, although this is less convincing. It is not conclusive whether VbX increases force attributes. This has been fraught by the type and parameters used for various muscle contractions, and the different sample populations that have varied in chronological age, experience and training status. VbX provides an insufficient stimulus to enhance cardiovascular indices, where VbX cannot increase heart rate to the same extent as conventional aerobic exercise. But when conventional aerobic exercise is not possible, for example, in aged, cardiovascular compromised persons, VbX could be implemented at an early stage because it could provide a safe induction of a slight elevation of cardiovascular function indices while providing neural and myogenic benefits. In conclusion, VbX is a safe modality to increase physiological responses of reflex and muscle activity, and muscle function, for athletes, the aged and compromised health. However, further research should focus on the optimum dose relationship of frequency, amplitude and duration for the various populations.